The Controversy of The Hijab for Students in State Schools During the New Order Era (1978-1991) - Zaeni, Azista Difanaya Khoirunisa (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
Hijab is a form of identity for Muslim women. Muslim women are required to cover their nakedness from head to toe except for the face, palms and soles of the feet. The ban on wearing the head scarf in public schools was considered an act of Islamic activism and religious primordialism by the New Order government. Hijab is an Arabic term which means loose clothing that covers the genitals from the shoulders to the feet, so it doesn't form curves. The use of headcarves for female students in public schools stems from the influence of the ITB Salaman Mosque da'wah movement and the PII (Indonesian Islamic Students) organization. The Iranian revolution of 1979 has increased the enthusiasm of santri and Islamic values, including the widespread use of the head scarf among young women. The prohibition and discrimination of wearing the head scarf during the New Order led to a polemic for religious organizations. Therefore, this article will examine the relationship between Muslim organizations and the New Order government and discrimination in the use of the head scarf in educational institutions during the New Order. To answer this problem, the writing of the article will use a descriptive analysis approach and data collection by conducting a literature search.